2008
DOI: 10.1111/j.1365-2702.2007.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia and assisted suicide in Dutch hospitals: the role of nurses

Abstract: Nurses in clinical practice are often closely involved in the last stage of a person's life. Consequently, they are often confronted with caring for patients requesting euthanasia or physician-assisted suicide. The results provide relevant information and may help nurses in defining their role in euthanasia and physician-assisted suicide, especially in case these practices should become legalised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 15 publications
(26 reference statements)
1
42
0
Order By: Relevance
“…[21,22] Alternatively, future research may set out to evaluate physician's knowledge and perceptions related to MAID in order to highlight any differences. As a healthcare provider's role in MAID varies based on occupation, it would be valuable to compare the results of these two populations to determine if any similarities or differences exist so educational resources can be tailored to specific groups of healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] Alternatively, future research may set out to evaluate physician's knowledge and perceptions related to MAID in order to highlight any differences. As a healthcare provider's role in MAID varies based on occupation, it would be valuable to compare the results of these two populations to determine if any similarities or differences exist so educational resources can be tailored to specific groups of healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…139 A smaller sample study (n=359) found that nurses were more likely to be consulted by the physician in cases where euthanasia was granted (81.4 per cent) than (71.6 per cent) where it was not. 140 Of 143 cases where a nurse was present during administration, in 3.5 per cent the nurse administered the euthanatica, and in 11.9 per cent the nurse administered the euthanatica with the physician. 141…”
Section: Involvement Of Nursesmentioning
confidence: 99%
“…One Dutch study recommended the use of Ô[m]ultidisciplinary institutional guidelinesÕ to improve collaboration between physicians and nurses and prevent the involvement of nurses in the administration of euthanatica, which Ôcontrasts sharply with the legal rules and the professional responsibilities of nursesÕ.Õ 355 The same study recognised that such multidisciplinary guidelines might not work in the homecare sector in the Netherlands, as a result of the way it is structured, but advocated the use of guidelines specifically for nurses in which Ôtheir role and responsibilities are clearly describedÕ. 356 Studies of nursesÕ involvement in Belgium have made similar recommendations in favour of guidelines.…”
Section: Involvement Of Nursesmentioning
confidence: 99%
“…4 The perceptions of registered nurses (RNs) have been rarely explored, although findings from countries that have legalized euthanasia emphasize their significant role in the process. [11][12][13][14] Since 2000, only 2 studies have explored Finnish nurses' views of euthanasia, 4,15 although its legalization would potentially affect more than 50 000 nurses in Finland. 16 …”
mentioning
confidence: 99%